Caracterización de las urgencias oftalmológicas en el Hospital José Joaquín Aguirre - Ivankovic L., Vania; Minaeff T., Tamara (Revista Hospital Clínico Universidad de Chile, 2009)
Objective: To perform an epidemiological data of the number and characteristics of patients who consult with ophthalmological emergencies in an Ophthalmology Service. Methods: A retrospective analysis was performed of all patients attending to the Ophthalmology Service of José Joaquín Aguirre Hospital with ophthalmic emergencies, during one-month period. Consultation distributions were determined by gender, age, consultation reason and final diagnosis. Results: of the 2056 consultations seen in the Ophthalmology Service during the monitoring period, only 60 patients came due to an emergency. 48% were men and 52% women. Ages of the sample ranged from 0 to 86 years, were the 51-70 years interval represented 43.3%; 23.3% were due to traumatic causes and 76.7% of non-traumatic origin. In 40% of the cases the reason of consultation was red eye, while the most common final diagnosis was acute conjunctivitis (28.3%). Patients who required control represented 31.7% and hospitalization was not considered necessary. Conclusion: the medical emergencies caused by eye problems are a major cause of disease, representing a significant proportion of the general ophthalmological consultations. Therefore, general doctors and other health professionals should be trained to identify, handle and refer to specialist if necessary, the most prevalent eye pathologies.